Методи синтезу та біологічна активність 1,2,4-триазол-3-тіонів - Каплаушенко, Андрій Григорович; Каплаушенко, А. Г.; Kaplaushenko, A.G. (My University, 2009)
Проведено аналіз і узагальнення літературних джерел, що містять дані відносно методів син‑ тезу 1,2,4-триазол-3-тіонів, які містять різноманітні замісники при N1 , N4, С5-атомах триазоло‑ вого циклу. Проаналізовані умови проведення синтезу відповідних 3-тіопохідних 1,2,4-триазолу. Проведен анализ и обобщены литературные источники, которые содержат данные относительно методов синтеза 1,2,4-триазол-3‑тионов, содержащих различные заместители при N1 , N4, С5-атомах триазолового цикла. Проанализованы условия проведения синтеза соответствующих 3‑тиопроизводных 1,2,4-триазола. The analysis is carried out and literature original sources are generalized. Literature original sources are contained information about 1,2,4-triazol-3-tions synthesis methods, which are contained various assistants at N1, N4, С5-atoms of triazol cycle. Conditions of synthesis of corresponding 1,2,4-triazols’ 3-thioderivatives are carried out.
Методы синтеза и биологическая активность 1,2,4-триазол-3-тионов
Synthesis methods and biological activity of 1,2,4-triazol-3-thions
Keywords: 1,2,4‑триазоли; методи синтезу; тіотриазолін; 1,2,4 ‑ триазолы; методы синтеза; тиотриазолин; 1,2,4-triazols; synthesis methods; thiotriazol